DFT study into the reaction mechanism of CO methanation over pure MoS2. Issue 16 (26th April 2018) - Li, Zhenhua; Zhang, Kan; Wang, Weihan; Wang, Baowei; Ma, Xinbin
Abstract: Mo‐based catalysts are commonly used in the direct methanation of CO; however, no integrated mechanism has been proposed due to limits in characterizing the nano‐sized active structures of MoS2 . Thus, we report our investigation into the mechanism of CO methanation over pure MoS2 through density functional theory simulations, considering that only MoS2 edge sites exhibit catalytic activity. Simulations revealed the presence of (010) and (110) surfaces on the MoS2 edges. Both surfaces are reconstructed by the redistribution of surface sulfur atoms upon exposure to H2 /H2 S, and after sulfur coverage redistribution, S vacancies are generated for CO hydrogenation. The reaction mechanisms on both surfaces are discussed, with the S‐edge being better suited to CO methanation than Mo‐edge on the (010) surface. The rate‐controlling step differs between surfaces, and corresponds to the initial activation reaction, which was achieved more easily on the (110) surface. Abstract : Considering the commonly accepted viewpoint that edge sites of MoS2 exhibit catalytic activity in methanation, density functional theory provides an insight into the species present on the edge surfaces, in which the (010) and (110) surfaces are presented, respectively. This study discusses the adsorption and reaction mechanism in detail to give a performance comparison corresponding to each catalytic surfaces.